OVERVIEW OF WORKERS' PULMONARY FAAL CONDITIONS AND WORKER ACTIONS AT THE END OF THE FINAL SCRUB INDUSTRY X SURABAYA - Maya Puspita Sari; Corie Indria Prasasti (Universitas Airlangga, 2020)
ABSTRACTOne type of air pollution that has the potential to harm human health is particulate dust. Particulate dust causes pulmonary damage when inhaled during work continuously. The purpose of this study was to see the description of the condition of the lung physiology ,workers' actions,worker smoking habits,use of respiratory tract,and physical quality of the environment. This was descriptive research, using design cross-sectional. The sample size used total population as 14 people. physical environmental quality includes PM2.5 concentration,air temperature and humidity. The action variable was measured using an observation sheet, while smoking habits and respiratory tract measured using a questionnaire. Lung function disorder was measured using spirometry. Based on the results,50% of workers had a bad action, 64.3% of workers had a smoking habit, and 28.6% of workers didn’t use continuous respiratory protection during working hours. The measurement of physical environmental quality at PM2.5 still meets the quality standard, while for the temperature and humidity do not meet quality standards. A total of 5 workers in the final rub section have lung function disorders. The conclusion that can be taken is more lung function disorder is experienced by workers who have smoking habits, not using continuous respiratory protection during working hours. The advice that can be given is that the use of the respiratory protector of masks should always be used continuously while workin. For workers with lung function disorders, should immediately conduct further medical examination and reduce smoking habits so that the lung physiological condition doesn’t decrease.Keywords: PM2.5 concentration, lung function disorders, workers' actions,worker smoking habits,use of respiratory protection